Pola Komunikasi Politik A.A Gede Agung Suyoga Kepada Anak Muda Kota Denpasar Dalam Pemilihan Legislatif Tahun 2019 - Krisna Adhi, I Dewa Putu Wahyu; Pramana, Gede Indra; Mahaswari Jayanthi Mertha, A.A Sagung Mirah (Jurnal Nawala Politika, 2020)
This research aims to find out how A.A Gede Agung Suyoga’s political communication patterns in the 2019 legislative elections. As the theoretical basis, this research uses the Theory of Generations by Karl Mannheim and Political Communicator Theory from Lasswel as a frame of the problem in this study. The research method used in this research is qualitative descriptive research with primary and secondary data usage. Agung Suyoga’s politics towards young people in the city of Denpasar. The result of this study are: first, the younger generation in groups Y and Z take the most dominant role in the procces of selecting Agung Suyoga as a member of the council. Second, Agung Suyoga’s political communication pattern can be seen through the activities, issues, and approaches he applies to the campaign procces.   Keywords :Political Communication, Agung Suyoga, Youth